Keeping Goats, (Sheep?), and Pigs at Deir el-Medîna - Sweeney, Deborah.
This article surveys the role that pigs, goats, and sheep played at the tomb-builders’ community of Deir el-Medîna. Pigs were probably present on site, but the presence of sheep and goats is more problematic. The same term, anx, refers to both animals, but the dry environment of the village is far more suitable for goats. Goats (and occasionally sheep) may have been kept at the village, herded near the Nile on their owners’ behalf, or simply bought as needed. Pigs may have been penned or allowed to roam freely. The provisions these animals required, their meat and milk yields, other products they generated, the social setting of animal ownership, the prices paid for them, and the possible hazards of keeping them, are also considered.   doi: http://dx.doi.org/10.5913/jarce.54.2018.a013